Social media and organ donation - A narrative review - Gopal Basu; Sanjeev Nair; Sibel Gokcay Bek; Prashant Dheerendra; Krishnam Raju Penmatsa; Karthikeyan Balasubramanian; Aakash Shingada; Arvind Conjeevaram (Indian Journal of Transplantation, 2021)
Increasing demand for organ transplantation which is often the lifesaving treatment for organ failure and a shortage of organs is a crisis prevalent in many countries. Proactive engagement of the society by improving awareness about organ donation is perceived to be the key to address the problem of organ shortage. In the current digital era, social media (SoMe) organ donation campaigns are one of the most practical and effective ways to disseminate information and promote collaboration among participants. Many governmental and nongovernmental organizations and social activists are utilizing popular SoMe platforms such as Facebook, Twitter, YouTube, and Instagram to promote organ donation awareness. Although such SoMe campaigns are impactful and open unique possibilities to address organ shortage, one should also be aware of the challenges of maintaining confidentiality, the potential for misuse, misinformation, and negative framing. In this narrative review, we review the use of SoMe to promote organ donation including its benefits, pitfalls, and attempt to list some recommendations.